DUKUNGAN KELUARGA PADA ANAK PENDERITA TUBERKULOSIS (TBC) DI DESA HARAPAN KECAMATAN PEMANGKAT - Stiya Fiola; Fatmawati Fatmawati; Riama Al Hidayah (Universitas Tanjungpura, 2020)
Abstract This research aimed to know how the support of family especially parents have child sufferers of tuberculosis in Desa Harapan, Kecamatan Pemangkat. The research method used was qualitative research with descriptive methods. Sources of research data is parents have child sufferers of tuberculosis. The data taken relates with thetotal sufferers of tuberculosis in Desa Harapan. The research results showed that the supports of family especially parents during the healing process of the disease is a form of biological, educationat, socialization, and protective support. The family supports of biological such as fulfillmen necessity of nutritional and take carethe child when they sick. The family supports of educational such as teaches cleanliness in the family.The family supports of socialization such as show and explain of medicine. The family supports of protective such as protect child disease and give medicine on time. Keywords: The Family Support, Tuberculosis